INCLUSIVE SOCIETY: MERAJUT TOLERANSI BERBANGSA BERBASIS AGAMA, SOSIAL-EKONOMI, DAN POLITIK LOKAL - Muhammad Zaki (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Meto, 2018)
The diversity that develop in the earth of Indonesia is sunnatullah and a necessity that cannot be rejected by anyone, whether they like or dislike. As an entity, the Indonesian people should make the diversity as a force in order to achieve the goal and noble ideals of Indonesian nation, is to bring prosperity for all people, both welfare and spiritual, vertical well-being or horizontal. The phenomenon that occurs in some Indonesian society at this time is the depletion of community inclusivism at various levels of life, thus becoming a problem for the integration and wholeness of the nation-state. This fact can be seen from the events that occur in the homeland these days, which feels very exclusive nuances, such as the growing understanding of radicalism, terrorism, religious politicization and intolerant attitudes in addressing a social issue. This happens because of various factors, such as the occurrence of irregularities in religious understanding for some adherents, the existence of political interests, and the existence of socio-economic problems. Therefore, the inclusive understanding of the community needs to be knit again by promoting the spirit of togetherness, openness and tolerance among fellow elements of the nation. This study aims to re-knit the concept of an inclusive Indonesian society and ready to accept the diversity and differences. The development of inclusive society in this study is based on differences in religious, socio-economic, and political perspectives that embraced by Indonesians.